Effectiveness of Giving Sleep Position of 45o Semifowler on Sleep Quality and Oxygen Saturation in Congestive Hearth Faillure Patients - Isrofah - Isrofah; Anik Indriono; Ifa Mushafiyah (LPPM STIKES KENDAL, 2020)
Congestive heart failure is a progressive health problem with high morbidity and mortality. Patients with heart failure by 30 million people and is a non-communicable disease (PTM) which causes the highest death in the world. The main symptoms of heart failure are chest pain and nocturnal dypsneu which disrupt sleep quality and decrease oxygen saturation. One of the treatments is by positioning (positioning), including the 45o semifowler sleeping position. This study aims to determine the effectiveness of giving a 45o semifowler sleep position on sleep quality and oxygen saturation in patients with Congestive hearth faillure at Batang Regional Hospital. The sampling technique was purposive sampling method. The sample in this study were 20 patients with Congestive hearth failure at Batang Hospital who experienced sleep disturbances and decreased oxygen saturation. Data collection used PSQI (Pittsburgh Sleep Quality Index) questionnaire and early warning scoring system checklist. Data analysis using the Wilcoxon Test.Based on the analysis using the Wilcoxon test obtained value of sleep quality significance p value 0.001 < α = 0.05 and significance of oxygen saturation p value 0,000 <α = 0.05 then Ha is accepted, which means giving a 45o effective semifowler sleep position on sleep quality and oxygen saturation in Congestive heart failure patients. Giving semifowler 45o sleep position is effective on sleep quality and oxygen saturation of Congestive heart failure patients in Batang District Hospital